Pengaruh Tindakan Disiplin, Pengawasan Internal dan Beban Kerja Terhadap Kinerja Anggota Polri di Polda Kepulauan Riau - Mahendra, Nyoman Ananta; Prianggono, Jarot; Sinaga, Saut Panggabean; Dhamayanti, Sylvia Kartika (Prisani Cendekia, 2025)
One of the factors that can improve employee performance is motivation. Motivation is a series of attitudes and values that influence individuals to achieve specific things in accordance with individual goals. An employee will be motivated at work, if the employee is in a pleasant work environment and gets fair number of maintenance factors is insufficient, it will cause job dissatisfaction. So the maintenance factor does not create job satisfaction but can prevent job dissatisfaction. This research was conducted by survey to a population of 376 Polri members in the Riau Islands Regional Police. Research with quantitative data processing and results show that there is an influence of disciplinary action to performance (89.72%), internal control to performance (8.88%) and workload to performance (4.6%). Thus it is clear that disciplinary action for police is the most important variable in improving performance in the field.